Residential Buildings Thermal Performance to Comply With the Energy Conservation Code of Saudi Arabia - AlFaraidy, F. A.; Azzam, S. (Engineering, Technology & Applied Science Research, 2019)
About half of the total generated electricity in Saudi Arabia (SA) is consumed for the air conditioning of residential buildings. To reduce this burden on the economy as outlined by the country’s 2030 vision, the implementation of the Saudi energy conservation code (SBC602) needs to be enforced. This code divided KSA into three climate zones with maximum overall heat transfer coefficients. This study aims to facilitate the use of thermal insulation by analyzing optimum thermal insulation thickness for each zone and calculate the payback period of initial insulation costs. Three cities were selected to represent the three climate zones, Riyadh, Arar, and Turaif. The code-compliant thermal insulation thickness is calculated using these variables: thermal properties of three insulation materials, overall heat transfer coefficients, and three insulated wall structures. It is concluded that external insulation and finish system utilizing polyurethane is the most feasible option with the best thermal performance. Polyurethane thicknesses are ranging from 45mm to 65mm, wall widths are ranging from 250mm to 320mm, while the overall costs are ranging from 20.02 to 24.57 US/m2. This system is used to conduct a comparison between energy-efficient-building and base-case-building in terms of cooling loads and electrical consumption using hourly-analysis-program (HAP) with international weather data. The simulated annual savings in energy consumption for the three zones are 67.4%, 66.56%, and 67.91%. The economic analysis shows promising payback years, which are 3.1, 3.9, and 4.3 for zone one, zone two and zone three respectively.